The relationship between perceived external prestige and perceived organizational justice and their impact on organizational cynicism - an analytical research in the faculties of Karbala universities - Meethaq Hatif Al-Fatlawii,; Dia Faleh Bnai, (Iraqi Journal for Administrative Sciences, 2025)
This research aims to test the relationship and the impact of each of the perceived external prestige and perceived organizational justice as variables independent of cynicism organization as a variable-response among a sample of the lecturers staff in the colleges of the University of Karbala totaled (250) lecturers, and to achieve this goal is the formulation of the research problem expressed as a set of questions, including (what is the level of influence of the perceived external prestige and perceived organizational justice perceived level of cynicism organizational lecturers colleges), for the purpose of access to the answers to those questions were formulated a number of assumptions, including (There correlation and effect for each of the perceived external prestige and perceived organizational justice in organizational cynicism) and design model Search illustrates the research hypothesesThe tools are used to measure several in the practical side, depending on the program of the statistical analysis (Spss v.21) The research found a set of results can be summarized that there is a correlation and effect and are opposite between each of the perceived external prestige and perceived organizational justice and variable-response (cynicism organizational) at the lecturers , and based on those results, the researcher presented a set of recommendations including the need to be aware of the Deanship of colleges that promote or interest the prestige of the external College works to generate awareness of the lecturers at the existence of organizational justice, which will reflect the impact of that perception by reducing the levels of organizational cynicism among the lecturers.